Authorial Recognition of the Production Design in Spanish Audiovisual Productions: An Analysis from the Profession´s Perspective - Iturbe Tolosa, Andoni; Palomino, Lorena; Collado, Puerto; López, Laura; Del Castillo Aira, Itxaso (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The manuscript's main objective is to assess the perception of production design professionals regarding authorship and recognition of their craft. The methodology combines both quantitative and qualitative perspectives. The surveyed sample (n=54) presents an even distribution by gender. 51.9% of the people surveyed consider that the biggest barrier they encounter along the way is the public's lack of knowledge about the role of the art department. Only 5.6% of the people surveyed felt that their work has not been undervalued compared to other roles (especially cinematography).